2010
DOI: 10.1186/1471-2458-10-696
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in cardiovascular incidence: results from the British Women's Heart and Health Study

Abstract: BackgroundPrevalence of cardiovascular disease (CVD) in women shows regional variations not explained by common risk factors. Analysis of CVD incidence will provide insight into whether there is further divergence between regions with increasing age.MethodsSeven-year follow-up data on 2685 women aged 59-80 (mean 69) at baseline from 23 towns in the UK were available from the British Women's Heart and Health Study. Time to fatal or non-fatal CVD was analyzed using Cox regression with adjustment for risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A number of well established cohort studies have been published showing that established risk factors such as systolic blood pressure and smoking account for a significant proportion of geographical inequalities in cardiovascular disease within the UK 4 5 8 12 29. However, these cohort studies do not directly address the impact of diet on geographical variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of well established cohort studies have been published showing that established risk factors such as systolic blood pressure and smoking account for a significant proportion of geographical inequalities in cardiovascular disease within the UK 4 5 8 12 29. However, these cohort studies do not directly address the impact of diet on geographical variation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of well established cohort studies have been published showing that established risk factors such as systolic blood pressure and smoking account for a significant proportion of geographical inequalities in cardiovascular disease within the UK. 4 5 8 12 29 However, these cohort studies do not directly address the impact of diet on geographical variation. For example, the British Regional Heart Study (a cohort of over 7000 men between 40 and 59 years of age recruited in 1978–80) found that variation in systolic blood pressure explained 27% of geographical variation in CHD incidence in Great Britain, body mass index explained 6%, and serum cholesterol levels had no affect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pooled estimate of our subgroup analysis showed that OCs do not impact BMI as well as FBG levels. Of note, emerging evidence showed the existence of regional disparities in cardiovascular disease incidence and mortality ( 87 , 88 ). Moreover, three-quarter of the world's CVD deaths occur in low- and middle-income countries ( 89 ).…”
Section: Discussionmentioning
confidence: 99%
“…To further validate our PRS results, we computed the PRS in Indiana Biobank datasets [31], European Prospective Investigation into Cancer (EPIC)-Norfolk [32], and the British women's heart and health study (BWHHS) [33][34][35] using the weights learned in the UK Biobank (Methods). In the Indiana Biobank [31], we have access to Afib and observed that for all metrics M-REGLE outperforms U-REGLE among European samples.…”
Section: M-regle Improves the Prs For Cardiovascular Traitsmentioning
confidence: 99%